The Evaluation of Variations of The Hyoid Bone with Multidetector Computerized Tomography - Gunes Bolatli; Nadire Unver Dogan; Zeliha Fazliogullari; Ali Sami Kivrak; Ismihan Ilknur Uysal; Ahmet Kagan Karabulut; Yahya Paksoy (Tropical Health and Medical Research, 2020)
The hyoid is a U shaped bone with a backward concavity. Locates at the lower edge of the mandible and lies parallel to the floor — functions as an attachment point for muscles and soft tissues of head and neck. The aim is to examine the variations and ossification of the hyoid. This study was performed retrospectively in 2010 - 2013 on 200 CT images. 3D volume rendering images of pure hyoid bone created from the axial CT images in 1 mm slice thickness. The morphological variation count was 23; ossification variations were 9 cases. No difference observed by gender, but there are differences between the age groups for ossification. Ossification rates were found as; partial 34 %, unilateral 33%, complete 22%, early 11%. Most of the morphologic variation were belong to minor horn (57%), variations of major horn were 30%. The clinical importance of hyoid bone has realized in recent years. Due to the close relationship of this bone with the muscles, ligaments, fascias, sternum, clavicles, its dysfunction can lead to general problems. Studies about the variations of hyoid bone found to be quite low, and we believe that our research will contribute to the content of literature.